Control of enzymatic browning of harvested 'Hong Huay' litchi fruit with hot water and oxalic acid dips - Kobkiat Saengnil (2018)
Pericarp browning considerably reduces the shelf life and value of litchi fruits. This research was aimed to evaluate three browning inhibitors for control of litchi browning. Litchi cv. Hong Huay fruits were dipped in hot water (98°C) for 30 s prior to soaking in solutions of oxalic, citric and ascorbic acids at 0,2.5, 5, 10, and 15% for 15 min. They were then stored at room temperature (25 ±1°C) and 74 % relative humidity for 5 days. The results showed that oxalic acid at a concentration of 10% was the most effective in controlling browning. Hot water dips enhanced the effectiveness of oxalic acid. Dipping in hot water, followed by treatment with oxalic acid, resulted in the retention of pericarp redness and gave the best browning inhibition during the storage time by reducing the activities of polyphenol oxidase and peroxidase and maintaining a high level of total anthocyanins.